In Freeze-All Strategy, Cumulative Live Birth Rate (CLBR) Is Increasing According to the Number of Blastocysts Formed in Women <40 Undergoing Intracytoplasmic Sperm Injection (ICSI) - Papanikolaou, Evangelos; Chartomatsidou, Tatiana; Timotheou, Evangelia; Tatsi, Petroula; Katsoula, Eleftheria; Vlachou, Christina; Asouchidou, Irene; Zafeiratis, Odysseas; Najdecki, Robert (Frontiers in Endocrinology, 2019)
Background: Elective freezing of all embryos, followed by frozen-thawed ET cycles emerged to prevent risk of Ovarian Hyperstimulation Syndrome and to allow endometrium recovery after Controlled Ovarian Stimulation, leading to better IVF outcomes. Blastocyst Freeze-all policy can minimize the number of abnormal embryos and consequently failed ETs, but its efficacy in terms of cumulative rates has not been studied yet. Methods: A prospective cohort observational study was carried out in Assisting Nature, Centre of Assisted Reproduction and Genetics, in Thessaloniki, Greece from January 2014 until December 2017. 244 patients, normal or high- responders, were analyzed. Women of 18-39 years underwent ICSI and Freeze-all policy at the blastocyst stage and achieved clinical pregnancy and/or live birth or had all their vitrified blastocysts transferred in subsequent frozen-thawed cycles. Women were divided into four groups (group A: 1-2 blastocysts frozen; group B: 3-4; group C: 5-6; group D ≥7 blastocysts frozen) or seven groups (group I: 1-2 blastocysts frozen, group II: 3, group III: 4, group IV: 5, group V: 6, group VI: 7; group VII: ≥8 blastocysts frozen), according to the numerical range or to the absolute number of vitrified blastocysts, respectively. Results: The main outcome of the study was the CLBR achieved by frozen-thawed ETs, according to the number of the vitrified blastocysts. Higher CLBR are expected, when at least 3 blastocysts are formed (group B: 65.2%) and at least 2 frozen-thawed ETs are performed, reaching highest rates (88%) by group D (≥7vitrified blastocysts). Similarly, CLBR is significantly increasing with the absolute number of the vitrified blastocysts, ranging from 20%, when 1-2 blastocysts are vitrified (group I) to 82.4% when ≥8 blastocysts are available. Conclusions: A higher number of vitrified blastocysts is associated with higher CLBR in women <40 years old- normal/high responders- following Freeze-all policy. Adopting Freeze-all strategy after blastocyst culture can contribute to improve delivery outcome after IVF, in terms of CLBR. The number of the total cryopreserved blastocysts produced might reflect the quality of the oocyte and can successfully predict the pregnancy outcome. The blastulation rate can be a robust criterion to segment or not an IVF cycle.